PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT GHMI LI INDONESIA - Halimah, Nur; Hendriati, Yossi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of leadership style, work motivation and work stress on employee performance at PT Ghim Li Indonesia. In this study, a quantitative method was used in which data were obtained from survey results and questionnaire data processing based on statistical procedures. Based on the sample in this study, there were 37 respondents. In this study, the results of the regression equation Y = 9.887 + 0.151X1 + 0.015X2 + 0.435X3 + e. Work stress variable has an effect on purchasing decisions with tcount (4.197) > ttable (2.0345), work motivation variable has no effect on employee performance with tcount (0.127) > ttable (2.0345), work stress variable has an effect on employee performance with tcount (4.197) > ttable (2.0345), and the variables of leadership style, work motivation, work stress influence simultaneously by showing the calculation results of fcount (9.321) > ftable (2.89) where if fcount > ftable. While the R2 value is 0.459 or 45.9% which indicates that the independent variables (X1, X2, X3) affect the employee performance variable (Y) by 45.9%, while the remaining 54.1% is influenced by other variables outside this study.